The Effect of Family Ownership, Profitability, and Sales Growth on Tax Avoidance in Manufacturing Companies on the Indonesia Stock Exchange for the Period 2020-2022 - Sari, Apri Lynia; Waluyo; Putra, Yananto Mihadi; Nugroho, Lucky; Ildiko, Orban (Economics & Islamic Finance Journal (ECIF), 2024)
This quantitative study aims to determine the effect of family ownership, profitability, and sales growth on tax avoidance. This study uses manufacturing companies listed on the IDX in 2020-2022. The sample selection of manufacturing companies in this study used the purposive sampling method, and the number of acceptable samples was 153 of the total number. Hypothesis testing in the study used panel data regression analysis with a significance level of 5% (0.05). The results of the test obtained: (1) there is no effect of family ownership on tax avoidance, (2) there is an effect of profitability on tax avoidance, and (3) there is an effect of sales growth on tax avoidance. The implication of this research is to provide information and references related to the variable determinants of tax avoidance in the manufacturing sector in the period 2020 to 2022.